Assessment of Inflammatory Markers in Psoriatic Patients - Naga Sridevi Illa; Pradeep Pendiyala (Asian Journal of Medical Research, 2019)
Background: Assessment of level of inflammatory markers in psoriatic patients. Subjects and Methods: Seventy- five psoriatic patients of either genders was selected and were divided according to PASI score into three groups (mild, moderate, and severe) each containing 25 patients. Twenty- five healthy subjects of age and sex matched were included as control. Correlations of ADA, hsCRP, SUA, and ESR with PASI scores were done. Results: There were 15 males and 10 females I mild group, 12 males and 13 females in moderate group, 14 males and 11 females in severe group and 13 males and 12 females in control group. The mean ADA level was 21.5 U/L in group I and 9.4 U/L in group II. The mean hsCRP level was 54.8 ng/ml in group I and 10.2 ng/ml in group II. The mean SUA level was 5.4 mg/dl in group I and 4.1 mg/dl in group II. ESR level was 28.6 mm/h in group I and 13.9 mm/h in group II. The difference was significant (P< 0.05). No significant correlation between PASI score and ADA, hsCRP, SUA, and ESR was found (P> 0.05).  Conclusion: Serum ADA, hsCRP, SUA, and ESR showed higher levels among psoriatic patients than healthy controls.